Application of Cumene Technology Mathematical Model; Procedia Chemistry; Vol. 15 : Chemistry and Chemical Engineering in XXI century (CCE 2015) - Chudinova A. I. Alena Igorevna; Salischeva A. Anastasiya; Ivashkina E. N. Elena Nikolaevna; Moyzes O. E. Olga Efimovna; Gavrikov А. А. Aleksey Alekseevich (2015, 2015)
Title screen